The Effect of Classical Lullaby Music Therapy on Anxiety in Primigravida Mothers in Labor - Nanik Sugiarti; Finta isti kundarti; Wiwin Martiningsih (Health and Technology Journal (HTechJ), 2025)
Anxiety during pregnancy is often intensified by the anticipation of labor and delivery, which can be overwhelming due to a lack of prior experience. The consequences of untreated maternal anxiety extend beyond the mother, potentially affecting fetal growth and long-term child development. This study aims to determine the effect of classical Lullaby music therapy on anxiety in primigravida pregnant women facing childbirth. The research design employed a quasi-experimental pretest-posttest control group design. The total sample in the experimental group was n = 30, and in the control group, n = 30, using a purposive sampling technique. The population in this study consisted of all primigravida pregnant women who visited the antenatal care clinic at the Sananwetan Health Center in March and April 2025. Based on the T-test, the mean data on the pretest is 39.40, and the posttest is 32.43. There is a decrease in the score of 6.967. The significance value (Sig. 2-tailed) is 0.000, which is <0.05, so it can be concluded that there is a significant influence. The test results show that H0 is rejected and H1 is accepted, which means that classical lullaby music therapy is more effective in reducing anxiety levels in primigravida mothers compared to the control group. Therefore, it can be concluded that classical lullaby music has a positive effect on primigravida mothers in facing childbirth. This type of music can be used as a therapeutic option for pregnant women experiencing anxiety.